2009
DOI: 10.1186/1423-0127-16-107
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus UL76 induces chromosome aberrations

Abstract: BackgroundHuman cytomegalovirus (HCMV) is known to induce chromosome aberrations in infected cells, which can lead to congenital abnormalities in infected fetuses. HCMV UL76 belongs to a conserved protein family from herpesviruses. Some reported roles among UL76 family members include involvement in virulence determination, lytic replication, reactivation of latent virus, modulation of gene expression, induction of apoptosis, and perturbation of cell cycle progression, as well as potential nuclease activity. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 43 publications
1
55
1
1
Order By: Relevance
“…The precise mechanism of cell cycle arrest induced by UL24 homologues remains to be clarified. An interesting and possible explanation is the recent report that HCMV UL76 induces chromosomal aberrations and DNA damage (Siew et al, 2009). Phosphorylation of ATM and -H2AX, accepted signals of DNA damage activation, were also observed for HSV-1 UL24 (our unpublished work), possibly revealing a conserved effect similar to the observed cell cycle arrest.…”
Section: The Ul24 Family: Multifunctional Virus Host Evasion Proteinsmentioning
confidence: 87%
See 1 more Smart Citation
“…The precise mechanism of cell cycle arrest induced by UL24 homologues remains to be clarified. An interesting and possible explanation is the recent report that HCMV UL76 induces chromosomal aberrations and DNA damage (Siew et al, 2009). Phosphorylation of ATM and -H2AX, accepted signals of DNA damage activation, were also observed for HSV-1 UL24 (our unpublished work), possibly revealing a conserved effect similar to the observed cell cycle arrest.…”
Section: The Ul24 Family: Multifunctional Virus Host Evasion Proteinsmentioning
confidence: 87%
“…Phosphorylation of ATM and -H2AX, accepted signals of DNA damage activation, were also observed for HSV-1 UL24 (our unpublished work), possibly revealing a conserved effect similar to the observed cell cycle arrest. It may be relevant that the number of cells with DNA damage breaks increased with increasing levels of the UL76 protein, a feature perhaps related to the putative endonuclease activity of the viral protein (Siew et al, 2009). Another example of this multi-functionality of virus host evasion proteins is the induction of the expression of interleukin-8 (IL-8) by the HCMV UL76 gene (our unpublished work).…”
Section: The Ul24 Family: Multifunctional Virus Host Evasion Proteinsmentioning
confidence: 99%
“…Previous studies have shown expression of HCMV-UL76 is not restricted to lytic replication and HCMV-UL76 can be detected in latently infected hematopoietic CD34+ cells and stable expression of HCMV-UL76 in glioblastoma cells inhibits viral replication in these cells [104,105]. Persistent expression of HCMV-UL76 in the cells and inhibition of viral replication leads to accumulation of multiple chromosome aberrations, chromosome misalignments, and increased formation of micronuclei containing activated DNA damage signal γ-H2AX [102].…”
Section: Promotion Of Tumorigenesis By Human Cytomegalovirus (Hcmv) Imentioning
confidence: 99%
“…HCMV-UL76 protein can induce DNA damage, apoptosis, cell cycle arrest [102] and inhibition of DNA repair machinery [103]. Previous studies have shown expression of HCMV-UL76 is not restricted to lytic replication and HCMV-UL76 can be detected in latently infected hematopoietic CD34+ cells and stable expression of HCMV-UL76 in glioblastoma cells inhibits viral replication in these cells [104,105].…”
Section: Promotion Of Tumorigenesis By Human Cytomegalovirus (Hcmv) Imentioning
confidence: 99%
“…Although endonuclease activity of UL76 has yet to be demonstrated, indirect evidence points to a role for UL76 in the chromosome breakage required for chromatin partitioning. For example, the presence of UL76 in uninfected cells is sufficient to stimulate chromosomal aberrations (Siew et al, 2009), and in HCMV-infected cells, UL76 is involved in stimulating a DNA damage response (Costa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%